Calcium-Induced Proteome Changes in Isolated Chloroplasts of Arabidopsis Thaliana - Bajwa, Azfar (fi=Turun yliopisto|en=University of Turku|, 2017)
Calcium is a well-known regulator of various biological processes, such as photosynthesis, resulting from responses to environmental cues that are recognized by specific calcium sensors, which give rise to intracellular signaling cascade responses. Its role as a secondary messenger in signaling has been emphasized recently. The calcium-dependent signaling network includes a large number of proteins, such as kinases, interacting at different levels with several targets. A response in the form of post-translational modifications (PTMs), in particular phosphorylation of target proteins, can be identified by proteomics methods. The aim of this study was to identify the calcium-dependent phosphorylation of proteins related to photosynthesis. In this work, a novel method for monitoring calcium-dependent phosphorylation was established. Ionomycin, a calcium-specific ionophore, was used in order to mimic natural calcium concentrations in chloroplasts during light (150nM) and during its transition to dark (10 µM). Additionally, Difference In-Gel Electrophoresis (DIGE) was used to screen and map differentially abundant proteins between chloroplasts treated with low and high levels of calcium. Finally, protein spots and their phospho-sites were identified by in-gel trypsin digestion, followed by mass spectrometry. Our study presents new target proteins involved in photosynthesis, which might be regulated by calcium signaling. Ferredoxin (Fd)-NADPH oxidoreductase (FNR)1, Variegated 2 (FTSH2) and ATPase alpha subunit (ATPA) were found to be phosphorylated in a calcium-dependent manner. In particular, FNR1, ATPA, Photosystem I reaction center subunit II-1 (PsaD) and Cytochrome b6-f complex iron-sulfur subunit (PetC) are proposed to contribute to Cyclic Electron Flow (CEF) in a calcium-dependent manner. Furthermore, Rubisco activase is suggested as a new calcium-dependent regulatory target of the Calvin-Benson-Bassham (CBB) cycle. Novel phospho-sites of proteins involved in the photosynthetic process are also reported. In future, this work will provide a basis to better understand signaling pathway(s) and the regulation of photosynthesis.